University of Shanghai Cooperation Organization (USCO) - a new model of international education (International relations and international law Journal, 2016)
The paper considers the improvement of higher education in the framework of the SCO integration projects. Nowadays more and more confident in the SCO declares himself integration in education. Cooperation and integration into the world educational space has become a major focus in the policy of Kazakhstan, development of the country’s foreign policy. Participation in this process is to increase the competitiveness of the Republic of Kazakhstan of educational services, the recognition of the skills of our scientists and teachers. Creating SCO creates the conditions for the implementation of joint educational programs, student mobility in the future. Kazakhstan will become a part of world education and the educational sector will cease to be a prime element of the social sphere, as an instrument through which the investments in the future of the country. The integration of scientific capacities naturally contributes to the development of innovative technologies in all spheres of life of the societies of the SCO member states. This means mobility in education, the ability to build personal training programs, listen to interesting subjects in any of the universities that are in the Shanghai Cooperation Organization. This system will provide a good leap in the quality of education. At the first stage of the SCO University introduced the following areas of training: regional studies, ecology, energy, IT-technologies.
Keywords: Human Capital; University of Shanghai Cooperation Organization (USCO); the sphere of education; international cooperation; competitiveness; process of integrationn; ecology; energy; IT-technology; regional studies; nanotechnology